Adaptiveness Of Equivalent Electrical Circuit For Vanadium Redox Flow Battery (V-RFB) Using Extended Kalman Filter (EKF) - S. F. M., Ibrahim; Mohd Rusllim, Mohamed; S., Razali; H., Ahmad; M. H., Sulaiman (2017)
Vanadium Redox Flow Battery (V-RFB) is a rechargeable battery and in order to store chemical potential it employs vanadium ions in different oxidation state. Kalman Filter (KF) generally applied to approximate the state of a system using measured input and output. Currently, studies on equivalent electrical circuit for V-RFB are inadequate in publications but available. This paper presents the proposed equivalent circuit for V-RFB that are suitable in any V-RFB system design and use Extended Kalman Filter (EKF) in MATLAB/Simulink for identification. The simulation result through a recursive EKF algorithm was analyzed and shows the adaptability of the circuit.